Solubility of CO2 in aqueous 2‑amino‑1, 3‑propanediol (Serinol) at elevated pressures - Abdul Samat, Nurul Fatin Nabilah; Yusoff, Rozita; Aroua, Mohamed Kheireddine; Ramalingam, Anantharaj; Kassim, Mohd Azlan (Elsevier, 2019)
In this work, aqueous 2‑amino‑1, 3‑propanediol solution (serinol) was investigated as a potential solvent for CO2 capture from different gas streams. Prior to CO2 solubility experiments, a qualitative prediction technique was performed on serinol to ensure its potentiality as a CO2 capture solvent. This was done using COSMO-RS approach based on quantum chemistry calculations. Based on this approach, serinol showed good affinity towards hydrogen–bond donors which proved to be beneficial in developing intermolecular interaction between serinol and CO2. The solubility of CO2 in serinol was then investigated at serinol concentrations ranging from 1 M to 3 M, temperatures ranging from 313.15 K to 353.15 K and CO2 partial pressures ranging from 1034.31 kPa to 2068.43 kPa. The solubility of CO2 in serinol reached a highest value of 1.64 mol of CO2/mol of serinol when the serinol concentration was 1 M, at 313.15 K and 2068.43 kPa. Meanwhile, Henry's law constant of CO2 in serinol was calculated using N2O analogy at 313.15 K and 333.15 K for molar concentrations of 1 M and 3 M of serinol. Results showed that the physical solubility of CO2 in serinol increased as the temperature and the concentration of the solution decreased. The lowest value of Henry's law constant of CO2 was 599.4 kPa·m3·kmol−1, for 1 M of serinol at 313.15 K. Furthermore, the recyclability of 3 M of serinol was investigated at 313.15 K and partial pressures ranging from 1034.31 kPa to 2068.43 kPa. At 1034.31 kPa, the solubility of CO2 in 3 M of aqueous serinol after the 3rd regeneration cycles were reduced to 72.73%.